The Negative Impact of Electrical Energy Subsidies on the Energy Consumption—Case Study from Jordan - Albatayneh, Aiman; Juaidi, Adel; Manzano-Agugliaro, Francisco (Energies (Basel), 2023)
Many developing countries subsidise energy (petroleum fuel products, natural gas and electricity), which was reflected in an extra pressure on the national budget, and this will support inefficient use of energy. In this study, the effects of electrical energy subsidies on the total electrical energy consumption in the residential sector were examined. Data on more than 260,000 Jordanian ordinary customers were collected, and the energy consumption of more than 1000 energy-extra subsidised Irbid District Electricity Distribution Company (IDECO) staff members was recorded over a 2-year period (2017 and 2018). These two groups were compared to examine the consequences of subsidising energy on the energy consumption and the consumption behaviour in the residential sector. The analysis revealed that ordinary householders consume around 296 kWh/month, while for the subsidised group 615 kWh/month was noted. Energy consumption increased during the summer and winter months, especially in the subsidised group, due to the heavy reliance on mechanical systems for cooling and heating. Electricity full price (without any subsidies) can be a very effective way to control the demand profile. It can be structured to encourage customers (generally those that have significant electricity demand) to reduce their total usage as well as peak demand (thus reducing the pressure on the grid and the power plant) by charging them full electricity prices.